2011
DOI: 10.1007/s00467-011-1921-y
|View full text |Cite
|
Sign up to set email alerts
|

Intensive hemodialysis for cardiomyopathy associated with end-stage renal disease

Abstract: Heart and kidney dysfunction often coexist, and increasing evidence supports the interaction of these two organs, as demonstrated by the clinical condition known as cardiorenal syndrome (CRS). We report a pediatric patient with end-stage renal disease (ESRD) who developed a dilated cardiomyopathy and decompensated heart failure after undergoing unilateral nephrectomy and while on maintenance peritoneal dialysis. He showed marked improvement in his cardiac function with the addition of intensive hemodialysis. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In agreement with recent daily dialysis studies, cardiac features as assessed by echocardiography were improved with intensive dialysis at home [ 23 , 24 , 25 , 26 ]. As shown in a subgroup of patients, left ventricular mass was reduced by 9.6% at 3 months, while the ejection fraction remained remarkably stable in the normal range of 61 to 62%.…”
Section: Discussionsupporting
confidence: 88%
“…In agreement with recent daily dialysis studies, cardiac features as assessed by echocardiography were improved with intensive dialysis at home [ 23 , 24 , 25 , 26 ]. As shown in a subgroup of patients, left ventricular mass was reduced by 9.6% at 3 months, while the ejection fraction remained remarkably stable in the normal range of 61 to 62%.…”
Section: Discussionsupporting
confidence: 88%
“…CRS 4 (CKD leading to heart failure) seems to be the least studied with most of the data restricted to case report/series. Nehus et al[ 36 ] described a case report of an 11-year-old child with end-stage kidney disease (ESKD) who developed a DCM and decompensated heart failure postunilateral nephrectomy while on maintenance peritoneal dialysis (PD). His electrocardiogram showed diffuse chamber enlargement, severely depressed biventricular function, and LVEF of 10%.…”
Section: Resultsmentioning
confidence: 99%
“…[ 35 ] AKI is a common complication in cases of sepsis, occurring in as many as 51% of patients in septic shock. [ 36 ] Activation of coagulation and fibrinolytic systems leads to endothelial injury, affecting filtration function. [ 37 ] Sepsis also affects cardiac and/or renal function via the renin–angiotensin–aldosterone system (RAAS) and hypothalamus–pituitary–adrenal axis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chan et al showed that nocturnal hemodialysis, which is an emerging mode of intensive hemodialysis, improved uremic clearance, Hb levels and hematopoietic progenitor cell function significantly in patients with ESRD (20). In a similar study by Nehus et al, cardiac function improved after beginning intensive hemodialysis in pediatric patients with ESRD (25). At the beginning of the present study, Hb concentrations were higher than 11 g/dL in 12.26% of the patients, while 62.29% had normal Hb concentrations, which indicates the effectiveness of the intervention.…”
Section: Discussionmentioning
confidence: 97%